Genomic and transcriptomic analysis of genes involved in exopolysaccharide biosynthesis by Streptococcus thermophilus IMAU20561 grown on different sources of nitrogen - Wang, Yuenan; Peng, Qingting; Liu, Yang; Wu, Na; He, Yanyan; Cui, Xinrui; Dan, Tong (Frontiers in Microbiology, 2024)
Exopolysaccharides (EPSs) produced by lactic acid bacteria contribute to improving the texture and functionality of fermented dairy products. In a previous study, four nitrogen sources were identified as affecting the yield, molecular weight and structure of EPSs produced by Streptococcus thermophilus IMAU20561 in M17 medium. In this genomic and transcriptomics study, a novel eps gene cluster responsible for assembly of repeating units of EPS is reported. This eps cluster (22.3 kb) consists of 24 open reading frames and is located in the chromosomal DNA. To explore EPS biosynthetic mechanisms we completed RNA-seq analysis of S. thermophilus IMAU20561 grown in four different nitrogen sources for 5 h (log phase) or 10 h (stationary phase). GO functional annotation showed that there was significant enrichment of differentially expressed genes (DEGs) involved in: amino acid biosynthesis and metabolism; ribonucleotide biosynthesis and metabolism; IMP biosynthesis and metabolism; and phosphorus metabolism. KEGG functional annotation also indicated enrichment of DEGs involved in amino acid biosynthesis, glycolysis, phosphotransferase system, fructose and mannose metabolism. Our findings provide a better understanding of S. thermophilus genetic traits, the biosynthetic pathways needed for production of EPS, and a theoretical basis for screening dairy starter cultures.